2018
DOI: 10.1021/acs.biomac.8b01298
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Radical Copolymerization of Cinnamic Derivatives as Renewable Vinyl Monomers with Both Acrylic and Styrenic Substituents: Reactivity, Regioselectivity, Properties, and Functions

Abstract: A series of cinnamic monomers, which can be derived from naturally occurring phenylpropanoids, were radically copolymerized with vinyl monomers such as methyl acrylate (MA) and styrene (St). Although the monomer reactivity ratios were close to zero for all the cinnamic monomers, such as methyl cinnamate (CAMe), cinnamic acid (CA), N-isopropyl cinnamide (CNIPAm), cinnamaldehyde (CAld), and cinnamonitrile (CN), they were incorporated into the copolymers and significantly increased the glass transition temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 98 publications
0
24
0
Order By: Relevance
“…Additionally, in the 1 H NMR spectrum of the obtained polymer, resonance peaks were observed for the methyl protons (H L , H M ) at the initiation chain-end derived from MTS near 0.5 and 1.0 ppm; the methoxy protons (H H , H I ) in the side chains and at the initiation chain-end, the methine protons (H E , H F ) in the main chain, and the methylene proton (H N ) at the termination chain-end in the region of 1.7-4.0 ppm; and the phenyl protons (H A , H B , H C ) in the side chains in the region of 5.5-7.5 ppm 19,23 . However, all the peaks were broad.…”
Section: Polymerization Of Cinnamates and Their Derivatives By Gtpmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in the 1 H NMR spectrum of the obtained polymer, resonance peaks were observed for the methyl protons (H L , H M ) at the initiation chain-end derived from MTS near 0.5 and 1.0 ppm; the methoxy protons (H H , H I ) in the side chains and at the initiation chain-end, the methine protons (H E , H F ) in the main chain, and the methylene proton (H N ) at the termination chain-end in the region of 1.7-4.0 ppm; and the phenyl protons (H A , H B , H C ) in the side chains in the region of 5.5-7.5 ppm 19,23 . However, all the peaks were broad.…”
Section: Polymerization Of Cinnamates and Their Derivatives By Gtpmentioning
confidence: 99%
“…As an alternative to these methods, Terao et al reported the copolymerization of cinnamic monomers with vinyl monomers, such as methyl acrylate or styrene, via living radical methods including metal-catalyzed living radical polymerization, atom transfer radical polymerization, reversible addition-fragmentation chain transfer polymerization, and nitroxide-mediated polymerization 19 . However, as the incorporation of cinnamic monomers into the copolymers ranged from 15 to 40 mol%, the obtained materials are unlikely to exhibit the properties expected for homopolymers of cinnamic compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to steric hindrance around the 1,2‐disubstituted vinyl group, cinnamic acids rarely homopolymerize . Although they are copolymerized with styrene and acrylate, their incorporation into the resulting copolymers is relatively low . Alternatively, hydroxy‐functionalized cinnamic acids such as ferulic acid are polymerized via condensation polymerization into bio‐based polyesters and polycarbonates using the hydroxy and carboxylic groups, though they lose the hydroxy functional groups upon polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The cinnamic acid family has a common structure, namely, (E)-3-phenyl-2-propenoic acid, which has phenyl and carboxylic acid groups attached to the 1,2-position of the vinyl group and thus can be regarded as a vinyl compound possessing both styrenic and acrylic structures. 17 However, due to steric hindrance around the 1,2-disubstituted vinyl group, cinnamic acids rarely homopolymerize. 18 Although they are copolymerized with styrene and acrylate, their incorporation into the resulting copolymers is relatively low.…”
mentioning
confidence: 99%